Perlindungan Hukum bagi Korban Catcalling secara Komprehensif - Azhar, Tengku Hanif; Hasibuan, Lidya Rahmadani; Nasutioni, Chairuni (IAI Nasional Laa Roiba Bogor, 2025)
Legal protection for victims of catcalling, which is a form of verbal sexual harassment. This study highlights the importance of legal recognition of victims' rights and the necessary remedial efforts to create a safe environment and respect the dignity of each individual. Catcalling is often considered a trivial act, but its impact on victims can be very detrimental. Comprehensive legal protection is needed to address this problem and provide a sense of security for the community, especially women. This study aims to analyze the existing legal framework and identify gaps that need to be fixed to provide better protection for victims of catcalling. In addition, this study also explores the remedial mechanisms that can be applied to support victims in the healing process. The methods used in this study include legal document analysis. This method involves reviewing various relevant legal documents, such as laws and regulations, policies, and other official documents. The aim is to identify the existing legal basis related to the protection of victims of catcalling. With this, this study is expected to provide a comprehensive understanding of the issue of catcalling and raise awareness of the need for effective legal protection for victims. Legal protection for victims of catcalling needs to be strengthened with clear recognition in the law and adequate remedial services. This step is expected to create a safer environment and respect individual rights.